Istota i zakres odnowy strategicznej w przedsiębiorstwach - Banaszyk, Piotr (The essence and the range of a strategic renewal in companies, 2005)
The article presents the issue of strategic renewal of the company. This concept was explained and defined. Then a methodology of the realization of strategic renewal and possible its trends was presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 399-405